KARAKTERISTIK BUTIR SOAL: CLASSICAL TEST THEORY VS ITEM RESPONSE THEORY? - Muh Syahrul Sarea; Rosnia Ruslan (Didaktika : Jurnal Kependidikan, 2019)
This research aimes to describe the characteristic of UAS items theme 1 at the fourth grade of Primary School in Paramasan bawah village according to the item difficulties and discrimination. The sample of this research was 37 students who took the final examination year academic 2018/2019. The objects of this research were question items and the answer sheet of the final exam that obtained from 3 different schools in Paramasan Bawah village. The data analysis technique used in this research was empirical analysis helped by Bilog  and Iteman program application. This analysis used to know the characteristic of items based on the Item Response Theory and Classical Test Theory. The result of this research showed the characteristic of UAS items, according to item response theory, 30 items had a good discrimination and 33 items had a good item difficulty, while according to Classical Test Theory: 15 items had a good discrimination and 27 items had a good item difficulty.Keywords: Characteristics of items, item difficulties, discrimination